-Able adjectives and the syntax of psych verbs. Issue 1 (20th June 2018) - Alexiadou, Artemis
Abstract : This paper deals with some restrictions on the formation of - able adjectives from object experiencer verbs in comparison to subject experiencer verbs, focusing on English and Greek. Building on Oltra-Massuet (2013 ), the paper assumes that there are two places of attachment for - able, a high one, which combines with a structure including passive Voice, and a low one, which combines with a smaller structure. While subject experiencer verbs combine with low - able in both languages, the behavior of object experiencer verbs is not uniform. The unavailability of high - able formation with object experiencer verbs is correlated with the unavailability of passivization. In English, only those object experiencer verbs that yield a well-formed passive can combine with high - able . In Greek, OE verbs do not form passives or - able adjectives. The differences between English and Greek are accounted for by appealing to differences in their Voice systems, with specific reference to passive formation.